Patterned film and article

JP2024079668A5Active Publication Date: 2025-03-12TOPPAN HOLDINGS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024017256
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2025-03-12
Estimated Expiration
2039-10-24

AI Technical Summary

Technical Problem

Existing methods for forming patterned films lack the ability to create films with specific structural variations, such as differing pattern densities and porosities, which are essential for advanced optical and functional applications.

Method used

A method involving the use of emulsions with dispersed particles that harden upon irradiation, combined with selective irradiation and liquid removal, to create patterned films with varying densities and porosities, allowing for controlled light scattering properties.

Benefits of technology

The method enables the production of patterned films with controlled light scattering properties and versatile applications, including image display and security features, without the need for a guide pattern or development step, and supports a wide range of pattern sizes from micro to milli orders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a patterned film with a special structure.SOLUTION: A patterned film 2 includes a plurality of portions with different pattern densities. At least one of the portions is porous. Compared to one of the at least one of the porous portions, the other at least one of the portions has a lower pattern density and porosity.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a patterned film. [Background technology]

[0002] Various methods have been reported for forming patterned films, including a method using irradiation with active energy rays such as ultraviolet rays or electron beams, and a method using self-organizing materials such as block copolymers. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2009-260330 A [Patent Document 2] JP 2016-197176 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a pattern film having a special structure. [Means for solving the problem]

[0005] According to a first aspect of the present invention, there is provided a patterned film comprising a plurality of portions having different pattern densities, one or more of the plurality of portions being porous, and one or more of the remaining portions having a lower pattern density and porosity compared to one of the one or more porous portions.

[0006] According to a second aspect of the present invention, there is provided an article comprising the pattern film according to the first aspect and a substrate supporting the pattern film. Effect of the Invention

[0007] According to the present invention, a patterned film having a special structure is provided. [Brief description of the drawings]

[0008] [Figure 1] 1 is a cross-sectional view illustrating a schematic view of a portion of an article according to a first embodiment of the present invention. [Diagram 2] FIG. 3 is a cross-sectional view illustrating another portion of the article according to the first embodiment of the present invention. [Diagram 3] FIG. 2 is a cross-sectional view illustrating an example of a state in which a film made of an emulsion is formed on a substrate. [Figure 4] FIG. 2 is a cross-sectional view illustrating an example of a state in which a particulate layer made of a hardened product of dispersed particles is formed in an area irradiated with ultraviolet light by patterned irradiation of ultraviolet light. [Diagram 5] FIG. 13 is a schematic cross-sectional view of an example where initiating removal of the second liquid from the film has resulted in coalescence of dispersed particles in non-irradiated areas. [Figure 6] FIG. 11 is a cross-sectional view showing an example of a state in which coalescence of dispersed particles further progresses in a non-irradiated region, and the coalesced dispersed particles penetrate and diffuse into a granular layer made of a hardened product of the dispersed particles. [Figure 7] FIG. 11 is a cross-sectional view showing an example of a state in which removal of the second liquid has been completed and the coalesced dispersed particles have completely moved to the granular layer. [Figure 8] FIG. 4 is a cross-sectional view illustrating an example of a state in which an uncured first liquid is cured by irradiation of the entire surface with ultraviolet rays. [Figure 9] FIG. 4 is a cross-sectional view illustrating a schematic view of a portion of an article according to a second embodiment of the present invention. [Figure 10] FIG. 6 is a cross-sectional view illustrating another portion of the article according to the second embodiment of the present invention. [Figure 11] FIG. 4 is a cross-sectional view illustrating a schematic view of a portion of an article according to a third embodiment of the present invention. [Figure 12] FIG. 11 is a cross-sectional view illustrating another portion of the article according to the third embodiment of the present invention. [Figure 13] 2 is a graph showing the particle size distribution of the first to third emulsions prepared in the examples. [Figure 14] 4 is a scanning electron microscope photograph showing a cross section of a line and space pattern formed by using the first emulsion and varying the line width and space width. [Figure 15] 4 is a scanning electron microscope photograph showing a cross section of a line and space pattern formed using the second emulsion and varying the line width and space width. [Figure 16] 11A to 11C are scanning electron microscope photographs showing cross sections of line and space patterns formed using the third emulsion and varying the line width and space width. [Figure 17] 16 is a graph showing concentration distribution obtained by image analysis of a part of the photograph in FIG. 15. [Figure 18] 17 is a graph showing the effect of the ratio of line width to space width on the standard deviation of the concentration distribution obtained by image analysis of the photographs of FIGS. 14 to 16 . [Figure 19] 6 is an optical microscope photograph showing the top surface of a line portion of a line and space pattern formed by using the first to third emulsions and varying the line width and space width. [Figure 20] 20 is a graph showing the effect of the ratio of line width to space width on the average density obtained by image analysis of the photograph of FIG. 19. [Figure 21] 20 is a graph showing the relationship between the standard deviation of the concentration distribution obtained by image analysis of the photographs of FIGS. 14 to 16 and the average concentration value obtained by image analysis of the photograph of FIG. 19. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The embodiment described below is a more specific embodiment of any of the above aspects. Elements having the same or similar functions are given the same reference numerals, and duplicated descriptions will be omitted.

[0010] [First embodiment] Fig. 1 is a cross-sectional view showing a part of an article according to a first embodiment of the present invention, and Fig. 2 is a cross-sectional view showing another part of the article according to the first embodiment of the present invention.

[0011] The article shown in FIGS. 1 and 2 includes a substrate 1 and a patterned film 2 . The material and shape of the substrate 1 are not limited. It is preferable that the substrate 1 has a smooth surface. For example, a film or a sheet can be used as the substrate 1.

[0012] The pattern film 2 is supported by a substrate 1. In the example shown in Figures 1 and 2, the pattern film 2 forms a line and space pattern. The pattern film 2 may form a pattern other than the line and space pattern.

[0013] The pattern film 2 includes a plurality of portions with different pattern densities. Here, the term "pattern density" means the ratio of the area of ​​the region where the pattern film 2 is located to the area of ​​the region where the pattern film 2 and its openings are located. For example, when the pattern film 2 forms a line and space pattern, the pattern density of a certain portion is calculated by dividing the width W of the line portion in this portion by the area of ​​the pattern film 2. L and the width of the space W S With W L +W S Width of the line part W L Ratio of W L / (W L +W S ).

[0014] Among the multiple portions included in the patterned film 2, one or more are porous. FIG. 2 illustrates an example of such a portion. The portion in FIG. 2 has a ratio W L / (W L +W S ) is larger. That is, the portion of FIG. 2 has a higher pattern density compared to the portion of FIG.

[0015] Among the multiple portions included in the pattern film 2, one or more other portions have a lower pattern density and porosity than one of the one or more porous portions. Such a portion may be porous or non-porous. FIG. 1 illustrates an example of a non-porous portion.

[0016] The pattern film 2 may include three or more portions with different pattern densities. In this case, one or more portions may be porous and two or more portions may be non-porous. Alternatively, two or more portions may be porous and one or more portions may be non-porous. In this case, among these three or more portions, the one with the lower pattern density preferably has a porosity equal to or less than that of the one with the higher pattern density. According to one example, the portion with a pattern density of 0.5 or less is non-porous, and the portion with a pattern density of 0.6 or more is porous.

[0017] This porosity correlates with the standard deviation of the concentration distribution obtained by image analysis of the cross section of the pattern film 2. The standard deviation of the concentration distribution obtained by image analysis of the cross section of a portion of the pattern film 2 having a pattern density of 0.6 or more is preferably 5 or more, and more preferably 10 or more.

[0018] The ratio of the maximum value to the minimum value of the standard deviation obtained for the multiple portions with different pattern densities is preferably 4.3 or more, more preferably 20.3 or more. When this ratio is small, the difference in porosity is also small. There is no upper limit to this ratio, but it is usually 30.0 or less.

[0019] For this image analysis, the image processing software Image J is used. Specifically, in each image of the cross section of the patterned film, an area that does not include areas that would cause contrast noise, such as fractures, is selected. Then, for each selected area, the standard deviation of the concentration distribution in a 256-level grayscale is extracted as a feature. If there are no pores (gaps between particles) in the selected area, the standard deviation is small, and the more pores there are, i.e., the higher the porosity, the larger the standard deviation. Therefore, the above ratio is an index of the porosity ratio.

[0020] The porosity of each part of the pattern film 2 is also correlated with the light scattering property of that part. The porosity of each part of the pattern film 2 is also correlated with the pattern density of that part. Therefore, the light scattering property of each part of the pattern film 2 is correlated with the pattern density of that part. Specifically, for multiple parts with different pattern densities, the average value of the concentration distribution obtained by image analysis of the surfaces of those parts has a positive correlation with the pattern density of those parts. This image analysis is performed by the same method as above.

[0021] For multiple parts with different pattern densities, the average value of the concentration distribution obtained by image analysis of the surfaces has a positive correlation with the light scattering properties of those parts. And the light scattering properties of each part of the pattern film 2 have a positive correlation with the porosity of that part. Therefore, for multiple parts with different pattern densities, the standard deviation of the concentration distribution obtained by image analysis of the cross sections of those parts has a positive correlation with the average value of the concentration distribution obtained by image analysis of those surfaces. This image analysis is performed in the same manner as above.

[0022] The pattern film 2 contains a hardened product 21b1 of dispersed particles, which will be described later, and a polymer phase 21b2.

[0023] The hardened product 21b1 of the dispersed particles forms the particulate layer 21b. The particulate layer 21b is a porous layer.

[0024] The polymerized phase 21b2 is located in the gaps between the particles contained in the granular layer 21b. In the lower pattern density portion of the pattern film 2, more of these gaps are filled with the polymerized phase 21b2 than in the higher pattern density portion. On the other hand, in the higher pattern density portion of the pattern film 2, more of these gaps are left unfilled with the polymerized phase 21b2 than in the lower pattern density portion. As a result, the above-mentioned difference in porosity occurs.

[0025] The pattern film 2 is made of, for example, a polymer material. Also, the pattern film 2 is made of, for example, the same material in its entirety. According to one example, the cured material 21b1 and the polymerized phase 21b2 are made of the same polymer material. In this case, the cured material 21b1 and the polymerized phase 21b2 may have the same or different degrees of polymerization. In the latter case, the cured material 21b1 may have a higher degree of polymerization than the polymerized phase 21b2.

[0026] 1 and 2, the polymerized phase 21b2 does not exist in the openings of the pattern made of the particulate layer 21b. The polymerized phase 21b2 may exist in the openings of the pattern made of the particulate layer 21b in the form of a layer thinner than the particulate layer 21b.

[0027] This pattern film 2 can be formed, for example, by the method described below (called the Emulsion Transforming Method for Patterning (ET method)). <Preparation of emulsion> First, an emulsion is prepared, which contains dispersed particles containing a first liquid that is cured by irradiation with active energy rays, and a dispersion medium containing a second liquid that is not cured by irradiation with active energy rays.

[0028] The emulsion may be an oil-in-water (O / W) emulsion or a water-in-oil (W / O) emulsion.

[0029] The dispersed particles include a first liquid that is cured by irradiation with active energy rays. Examples of active energy rays include visible light, ultraviolet rays, electron beams, and X-rays. For example, an acrylic monomer or oligomer, a methacrylic monomer or oligomer, an epoxy monomer or oligomer, or a mixture containing one or more of them can be used as the first liquid. As the first liquid, it is preferable to use an acrylic monomer or oligomer, or a methacrylic monomer or oligomer, because of advantages such as a wide range of options and a large degree of freedom in adjusting physical properties. For example, trimethylolpropane triacrylate can be used as the first liquid. The ratio of the monomer and oligomer in the first liquid is, for example, 30 to 100 mass %.

[0030] In addition, there are more types of lipophilic liquids that harden when exposed to active energy rays than there are hydrophilic liquids, so O / W emulsions offer greater freedom in material selection than W / O emulsions.

[0031] The dispersion medium includes a second liquid that does not cure upon irradiation with active energy rays. When the first liquid is lipophilic, the second liquid can be a hydrophilic liquid, such as water, a lower alcohol such as methanol or ethanol, or a mixture thereof. On the other hand, when the first liquid is hydrophilic, the second liquid can be a lipophilic liquid, such as an isoparaffinic solvent or mineral spirits.

[0032] The size of the dispersed particles depends on the size of the pattern to be formed, but it is preferable that the dispersed particles have an average particle size of 0.5 μm to 0.5 mm. Here, the "average particle size" is the weight average diameter obtained by particle size distribution measurement according to a laser diffraction / scattering method. If the dispersed particles have the above size, the uncured first liquid can efficiently penetrate into the gaps between the particles in a later process.

[0033] The proportion of dispersed particles in the emulsion is preferably 25% by mass or more. When the dispersed particles occupy the above proportion in the emulsion, the temperature of the area irradiated with active energy rays can be increased by effectively utilizing the heat of polymerization, thereby destabilizing the dispersion state of the dispersed particles containing the first liquid and forming an aggregate layer at the same time. The upper limit of the proportion of dispersed particles in the emulsion is not particularly limited as long as it is within a range in which phase inversion of the emulsion does not occur. According to one example, this proportion is 70 to 80% by mass or less.

[0034] The first liquid may further contain a photopolymerization initiator. As the photopolymerization initiator, a known photopolymerization initiator, for example, an alkylphenone-based photopolymerization initiator, can be used. As an alkylphenone-based photopolymerization initiator, for example, 1-hydroxycyclohexyl phenyl ketone can be mentioned. The first liquid may contain the photopolymerization initiator in an amount of, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the total amount of the monomer and oligomer.

[0035] When the emulsion is, for example, an O / W type, the dispersed particles may contain a hydrophobe in addition to the first liquid. Examples of the hydrophobe include higher alcohols with low solubility in water, such as cetyl alcohol, hexadecane, polymerizable monomers with relatively high molecular weights of the hydrocarbon chain, such as lauryl methacrylate and stearyl methacrylate, hydrophobic dyes, and polymers, such as polymethyl methacrylate and polystyrene. The hydrophobe plays a role in stabilizing the emulsion. The hydrophobe can be contained in an amount of, for example, 0.1 to 10 parts by mass relative to 100 parts by mass of the first liquid.

[0036] The dispersion medium may further contain a surfactant. For example, a commercially available surfactant for emulsion polymerization can be used as the surfactant. For example, a sulfosuccinate type surfactant such as dioctyl sodium sulfosuccinate can be used as the surfactant. The emulsion can contain the surfactant in an amount of, for example, 0.1 to 5.0% by mass based on the total mass of the emulsion.

[0037] In the case of O / W type emulsions, the dispersion medium generally contains a surfactant in order to ensure emulsification and the stability of the dispersed particles. In addition, the O / W type emulsion may contain a water-soluble polymer, cellulose nanofiber, or the like in the dispersion medium in order to improve the long-term storage stability of the emulsion. Furthermore, the O / W type emulsion may contain a viscosity modifier or an antifoaming agent in the dispersion medium as necessary.

[0038] On the other hand, in the case of a W / O type emulsion, in order to prepare a stable emulsion, the dispersion medium may contain a nonionic surfactant or a polymeric dispersion stabilizer having a suitable hydrophilic-lipophilic balance (HLB) value. If necessary, it is also effective for the W / O type emulsion to contain an ionic surfactant in the dispersion medium.

[0039] The emulsion can be prepared by utilizing known emulsification / dispersion techniques, such as a paint shaker, an ultrasonic homogenizer, a colloid mill, a homogenizer, and a membrane emulsification method.

[0040] <Membrane formation> Next, a film made of the emulsion is formed on a substrate. Hereinafter, the "film made of emulsion" is also referred to as a liquid film. Specifically, the liquid film can be formed on the substrate by applying the emulsion onto the substrate. Any substrate can be used as the substrate, and for example, a film or a sheet can be used.

[0041] The coating method is not particularly limited, but an appropriate coating method such as die coating, comma coating, or curtain coating can be selected depending on the thickness of the liquid film. The thickness of the liquid film can be, for example, 10 to 3000 μm. In addition, when a small amount of emulsion is applied to form a liquid film with a small area, a dispenser or the like can be used as necessary.

[0042] Fig. 3 is a schematic diagram showing an example of a state in which a film made of an emulsion is formed on a substrate. In Fig. 3, a film 2a made of an emulsion composed of dispersed particles 21a and a dispersion medium 22 is formed on a substrate 1.

[0043] <Irradiation with active energy rays> Next, the formed film is irradiated with active energy rays in a pattern such that the pattern film 2 finally obtained contains a plurality of portions having different pattern densities.

[0044] As described above, examples of the active energy ray include ultraviolet rays, electron beams, X-rays, etc. Pattern irradiation can be carried out, for example, by selectively irradiating the active energy ray through a mask or the like, or by selectively irradiating the laser beam.

[0045] By the patterned irradiation of the active energy rays, the first liquid contained in the dispersed particles is polymerized and cured in the area irradiated with the active energy rays (hereinafter also referred to as the irradiated area), thereby forming a granular layer made of the cured product of the dispersed particles.

[0046] FIG. 4 shows a schematic example of a state in which a particulate layer made of a hardened product of dispersed particles is formed in an area irradiated with ultraviolet light by patterned irradiation of ultraviolet light.

[0047] 4, in the area irradiated with ultraviolet light, the first liquid contained in the dispersed particles 21a is polymerized and hardened, and the dispersed particles 21a become hardened dispersed particle material 21b1. The hardened dispersed particle material 21b1 aggregates and stacks, and as a result, a granular layer 21b made of the hardened dispersed particle material 21b1 is formed. The pattern made of this granular layer 21b includes a plurality of portions with different pattern densities, similar to the pattern film 2 finally obtained.

[0048] In the region irradiated with ultraviolet light, the second liquid contained in the dispersion medium 22 does not harden, and therefore the dispersion medium 22 exists in the granular layer 21b, specifically, in the gaps between the hardened substances 21b1. On the other hand, in the region not irradiated with ultraviolet light (hereinafter also referred to as the non-irradiated region) in FIG. 4, the first liquid contained in the dispersion particles 21a remains unhardened.

[0049] The present inventors believe that the mechanism behind the aggregation of the cured material 21b1 in the irradiated region is as follows.

[0050] Irradiation with active energy rays causes polymerization heat in the dispersed particles 21a, which increases the temperature of the irradiated area. This temperature increase causes the surfactant adsorbed to the surface of the dispersed particles 21a to stabilize the dispersion of the dispersed particles 21a to be desorbed. This reduces the surface potential of the dispersed particles 21a in which polymerization has progressed. As a result, the dispersion of the dispersed particles 21a or their cured product 21b1 becomes unstable, and particle aggregation is promoted. In addition, in the process in which the particles aggregate and come into contact with each other, polymerization crosslinking may occur between the particles.

[0051] Moreover, this aggregation is completed before the surfactant that has been desorbed due to the temperature rise caused by the heat of polymerization is re-adsorbed onto the particles, so that the aggregated particles maintain their aggregated state without being redispersed.

[0052] The aggregation of the cured material 21b1 in the irradiated area may be promoted by incorporating a crosslinking agent in the dispersion medium in advance, which facilitates crosslinking between particles upon irradiation with active energy rays, thereby promoting particle aggregation.

[0053] <Removal of the second liquid> After irradiation with active energy rays, at least a part of the second liquid is removed from the film. In this step, at least a part of the second liquid may be removed, but the entire second liquid may be removed. The second liquid may be removed, for example, by drying the film. The drying is preferably performed until the amount of the second liquid is 30% by mass or less of the amount of the second liquid immediately after the liquid film is formed, and more preferably until the amount is 5% by mass or less. The second liquid may be removed by leaving the film at room temperature, but is preferably removed by heating and drying the film. The heating and drying can be performed, for example, by heating the film at a temperature in the range of 40 to 100° C. for 0.1 to 1 hour. By removing the second liquid, at least a part of the uncured first liquid can be moved from the area not irradiated with active energy rays to the granular layer consisting of the cured product of the dispersed particles.

[0054] In this step, by removing the second liquid, at least a part of the uncured first liquid is moved from the non-irradiated region to the granular layer made of the cured product of the dispersed particles. The movement of the uncured first liquid from the non-irradiated region to the granular layer may be performed so that all of it moves to the granular layer, or only a part of it moves to the granular layer.

[0055] In this method, it is not necessary to carry out a development step after irradiation with active energy rays, that is, removal of the uncured first liquid using a developer.

[0056] 5 to 7 show an example of a change in the state of the film caused by the removal of the second liquid. FIG. 5 shows an example of a state in which the coalescence of dispersed particles occurs in the non-irradiated area by starting the removal of the second liquid from the film. FIG. 6 shows an example of a state in which the coalescence of dispersed particles further progresses in the non-irradiated area, and the coalescence of dispersed particles penetrates and diffuses into the granular layer made of the hardened dispersed particles. FIG. 7 shows an example of a state in which the removal of the second liquid is completed and the coalescence of dispersed particles has completely moved to the granular layer.

[0057] When a part of the second liquid contained in the dispersion medium 22 is removed from the film 2a, the second liquid filling the gaps between the particles in the granular layer 21b is reduced in the irradiated region, and the second liquid is reduced in the non-irradiated region, and the dispersed particles 21a coalesce to form coalesced bodies 21a', as shown in Fig. 5. Then, as shown in Fig. 6, the uncured first liquid forming the coalesced bodies 21a' penetrates into the gaps in the granular layer 21b and diffuses into the granular layer 21b. This penetration and diffusion is believed to proceed due to capillary forces.

[0058] When the removal of the second liquid is complete, the migration of the uncured first liquid from the non-irradiated area to the granular layer 21b is also complete. As a result, for example, the structure shown in Fig. 7 is obtained. Note that when the second liquid is completely removed from the film, the only liquid remaining in the film is, for example, the liquid constituting the dispersed particles 21a or the combined particles 21a' thereof.

[0059] As described above, the pattern made of the granular layer 21b includes a plurality of portions with different pattern densities, similar to the finally obtained pattern film 2. As will be described below, the amount of the first liquid that penetrates into the gaps in the granular layer 21b differs between the portions with lower pattern density and the portions with higher pattern density.

[0060] That is, around the areas with lower pattern density there is a larger non-irradiated area, and therefore a larger amount of the first liquid, whereas around the areas with higher pattern density there is a smaller non-irradiated area, and therefore a smaller amount of the first liquid.

[0061] As a result, in the area where the pattern density is lower, a larger amount of the first liquid penetrates into the gaps in the granular layer 21b, for example, the entire gaps are filled with the first liquid.

[0062] On the other hand, in areas where the pattern density is higher, a smaller amount of the first liquid penetrates into the gaps in the granular layer 21b, for example, only a portion of the gaps is filled with the first liquid.

[0063] <Establishing the pattern> Finally, the uncured first liquid contained in the film from which the second liquid has been removed is cured. The uncured first liquid can be cured, for example, by irradiating the entire film with active energy rays. This forms a patterned film.

[0064] FIG. 8 shows a schematic diagram of an example of the state in which the uncured first liquid is cured by irradiating the entire surface with ultraviolet light. As shown in FIG. 8, when the entire film is irradiated with ultraviolet light, the uncured first liquid is cured by polymerization. As a result, a polymerized phase 21b2 is formed. Furthermore, in the cured material 21b1 constituting the granular layer 21b, further polymerization proceeds due to the irradiation with ultraviolet light. As a result, a pattern film 2 consisting of the cured material 21b1 of the dispersed particles and the polymerized phase 21b2 is formed.

[0065] As described above, before the entire surface is irradiated with ultraviolet light, in the granular layer 21b, in the portion having a lower pattern density, the entire gaps are filled with the first liquid, and in the portion having a higher pattern density, only a portion of the gaps are filled with the first liquid. Therefore, in the pattern film 2 obtained by irradiating the entire surface with ultraviolet light, the portion having a higher pattern density has a higher porosity than the portion having a lower pattern density.

[0066] As described above, the uncured first liquid can be cured after all of the uncured first liquid present in the non-irradiated region has moved from this region to the granular layer. Alternatively, the uncured first liquid can be cured when only a part of the uncured first liquid present in the non-irradiated region has moved from this region to the granular layer. For example, the entire film may be irradiated with active energy rays before the second liquid is completely removed from the film (i.e., at a stage in the middle of the first liquid in the non-irradiated region penetrating and diffusing into the granular layer), for example, at the stage shown in FIG. 6. In this way, a pattern film having a thickness in the non-irradiated region and a thicker irradiated region than the non-irradiated region can be obtained.

[0067] <Effects> As described above, the pattern film 2 includes a plurality of portions having different pattern densities. Of these portions, one or more are porous, and the other one or more have a lower pattern density and porosity. Therefore, in an article having the pattern film 2, the regions corresponding to the portions having a higher pattern density have a higher light scattering property than the regions corresponding to the portions having a lower pattern density. Therefore, this article can display, for example, an image or a pattern by utilizing the difference in light scattering property.

[0068] Moreover, this pattern film 2 can be formed in a self-organizing manner by simply irradiating the emulsion film with active energy rays in a pattern and then removing the second liquid. This method does not require a guide pattern to be provided on the substrate in advance, and does not require a development process. Therefore, this pattern film 2 can be manufactured by a simple method.

[0069] In addition, while the pattern size that can be realized by the conventional technology is, for example, a line width of several nm to several hundreds μm and a height difference of several nm to several hundreds μm, the above method can realize a wide range of pattern sizes. For example, the above method can form a pattern film having a large line width or height difference, for example, a line width of the micron order to the millimeter order and a height difference of the micron order to the millimeter order. As an example, the above method can form a pattern film having a line width in the range of 10 μm to 5 mm and a height difference in the range of 10 μm to 2 mm.

[0070] Furthermore, the above method has excellent controllability over the shape and size of the pattern, making it possible to form pattern films of various shapes and sizes.

[0071] [Second embodiment] Fig. 9 is a cross-sectional view that shows a schematic view of a part of an article according to a second embodiment of the present invention, and Fig. 10 is a cross-sectional view that shows a schematic view of another part of an article according to the second embodiment of the present invention.

[0072] The article according to the second embodiment is similar to the article according to the first embodiment, except for the following points. That is, the article according to the second embodiment further includes a layer 3 attached to the substrate 1 with the patterned film 2 sandwiched therebetween, as shown in Figs. 9 and 10. The layer 3 may have a single-layer structure or a multi-layer structure. According to one example, the layer 3 serves as a protective layer that protects the patterned film 2 from damage.

[0073] The layer 3 is attached to the substrate 1 and the patterned film 2 by an adhesive layer 4. The adhesive layer 4 is made of an adhesive or a pressure sensitive adhesive. The adhesive layer 4 fills the gaps in the patterned film 2. Since the adhesive layer 4 usually has a different refractive index from the patterned film 2, this article also exhibits the same optical effect as the article according to the first embodiment.

[0074] The adhesive layer 4 does not have to fill the gaps in the pattern film 2. An article having such a structure also exhibits the same optical effects as the article according to the first embodiment.

[0075] Furthermore, in this article, the ease of peeling of layer 3 may differ between positions corresponding to the higher pattern density portions and positions corresponding to the lower pattern density portions. For example, the adhesive strength to layer 3 may differ between the higher pattern density portions and the lower pattern density portions due to differences in their structures. Furthermore, the ease of brittle fracture may differ between the higher pattern density portions and the lower pattern density portions due to differences in their structures. Thus, this article can be used, for example, as a brittle label in which one of the layers undergoes brittle fracture when an attempt is made to peel it off from another article to which it is attached.

[0076] Instead of attaching the layer 3 via the adhesive layer 4, a coating liquid may be applied onto the substrate 1 and the pattern film 2, and the coating may be cured. The layer thus obtained may also be used, for example, as a protective layer.

[0077] [Third embodiment] Fig. 11 is a cross-sectional view that shows a schematic view of a part of an article according to a third embodiment of the present invention, and Fig. 12 is a cross-sectional view that shows a schematic view of another part of an article according to the third embodiment of the present invention.

[0078] The article according to the third embodiment is similar to the article according to the first embodiment, except for the following points: That is, the article according to the third embodiment further includes a color material 5 supported on the pattern film 2, as shown in Fig. 11 and Fig. 12. The color material 5 is, for example, a dye, a pigment, or a combination thereof.

[0079] In the pattern film 2, a portion having a higher pattern density carries a larger amount of color material 5 than a portion having a lower pattern density. Therefore, in this article, a region corresponding to a portion having a higher pattern density is more strongly colored than a region corresponding to a portion having a lower pattern density. Therefore, this article can display, for example, a colored image or a colored pattern such as a wood grain pattern. The surface of the substrate 1 may or may not carry the color material 5.

[0080] This article is produced, for example, by the following method. First, an article according to the first embodiment is manufactured. Next, a color material 5 is supplied to this article, and excess color material 5 is removed. Alternatively, a solution or dispersion liquid containing the color material 5 is supplied to this article, and the solvent or dispersion medium is removed.

[0081] As described above, the higher pattern density portion of the pattern film 2 has a higher porosity than the lower pattern density portion. Therefore, the former has a higher adsorption ability than the latter. Therefore, this method can obtain an article in which the higher pattern density portion and the lower pattern density portion carry different amounts of color material 5.

[0082] [Fourth embodiment] The coloring method described in the third embodiment can also be applied to, for example, security technology, as will be described below.

[0083] In the article according to the first embodiment, the region corresponding to the part with higher pattern density has higher light scattering properties than the region corresponding to the part with lower pattern density. Therefore, when the substrate 1 is colored, the region corresponding to the part with higher pattern density appears, for example, white, the region corresponding to the part with lower pattern density appears to be the color of the substrate 1 or a color close thereto, and the region corresponding to the opening of the pattern film 2 appears to be the color of the substrate 1. Also, when the substrate 1 is colorless and transparent and the background of the article is colored, the region corresponding to the part with higher pattern density appears, for example, white, the region corresponding to the part with lower pattern density appears to be the color of the background or a color close thereto, and the region corresponding to the opening of the pattern film 2 appears to be the color of the background.

[0084] In contrast, when the substrate 1 is white or the substrate 1 is colorless and transparent with a white background, the areas corresponding to the higher pattern density areas, the areas corresponding to the lower pattern density areas, and the areas corresponding to the openings of the pattern film 2 all appear white. That is, in this case, the pattern film 2 constitutes a latent image that is visualized by coloring it with the method described in the third embodiment. Therefore, when this article is used as a security element on which a latent image is recorded, the latent image is visualized with the coloring method described in the third embodiment, and the authenticity can be determined by confirming this visualized image. EXAMPLES

[0085] <Preparation of first emulsion> An O / W emulsion was prepared using the following ingredients: Monomer or oligomer: Trimethylolpropane triacrylate (Light Acrylate (registered trademark) TMP-A manufactured by Kyoeisha Chemical Co., Ltd.) Photopolymerization initiator: 1-benzoylcyclohexanol (Lunacure® 200 available from DKSH Japan) Surfactant: Sodium dioctyl sulfosuccinate (Sanyo Chemical Industries, Ltd., Sanmorin (registered trademark) OT-70) Second liquid: Distilled water First, 0.375 g of Lunacure (registered trademark) 200, 0.259 g of Sanmorin (registered trademark) OT-70, and 7.5 g of Light Acrylate (registered trademark) TMP-A were added in this order to a brown vial with a capacity of 50 mL, and the mixture was subjected to a rotational mixing process on a ball mill roll. Next, 9 g of distilled water was further added to the vial, and the mixture was subjected to an emulsification dispersion process. The emulsification dispersion process was performed by propeller stirring. The propeller rotation speed was 738 rpm, and the stirring time was 10 minutes. Then, the vial was subjected to rotational mixing for 2 hours. In this manner, a first emulsion was prepared.

[0086] <Preparation of the second emulsion> The second emulsion was prepared in the same manner as described above for the first emulsion, except that the emulsification and dispersion treatment was carried out using a paint shaker (Paint Shaker PC1171 manufactured by Asada Iron Works Co., Ltd.), and shaking with the paint shaker was carried out for 30 seconds.

[0087] <Preparation of the third emulsion> The third emulsion was prepared in the same manner as described above for the first emulsion, except that the emulsification and dispersion treatment was performed by hand shaking, which was performed 10 times.

[0088] <Measurement of particle size distribution> The particle size distribution and average particle size were measured for each of the first to third emulsions. For this measurement, a measurement system was used, which was a particle size distribution measuring device Microtrac MT3300EXII manufactured by Nikkiso Co., Ltd., equipped with a liquid circulation pump Microtrac USVR manufactured by Nikkiso Co., Ltd., and the weight average diameter was obtained as the average particle size. The obtained emulsion was composed of dispersed particles (hereinafter also referred to as emulsion droplets) containing the first liquid and a dispersion medium containing the second liquid. The average particle sizes of the first to third emulsions are summarized in Table 1 below. The particle size distributions of the first to third emulsions are also shown in FIG. 13.

[0089] [Table 1]

[0090] <Membrane formation> Using each of the first to third emulsions, a plurality of films were formed by the following method. First, five layers of 20 mm wide, 80 μm thick masking tape manufactured by 3M were attached to the surface of a microscope slide glass. The center of this five-layer laminate was cut out into a rectangular shape, thereby producing a cell (hereinafter referred to as a liquid reservoir cell) having a depth of 400 μm and an opening dimension of 10 mm × 30 mm.

[0091] Next, 112 μL of the emulsion was collected using a micropipette and spread and filled into a liquid-reservoir cell, forming a membrane (i.e., liquid membrane) made of the emulsion with a thickness of approximately 375 μm, calculated taking into account the specific gravity.

[0092] <UV irradiation> A copper mask having a thickness of 0.25 mm and having stripe-shaped openings was placed on the liquid film via an aluminum spacer having a thickness of 1 mm so as not to come into contact with the liquid surface. Here, a number of masks were used as the copper mask, each of which had stripe-shaped openings corresponding to the line and space pattern and had different widths of the line and space portions.

[0093] Next, a UV parallel light exposure machine (SAN-EI ELECTRONIC UVC-2502S) was used to expose the sample to 4.6 mW / cm2. 2 By irradiating the mask with ultraviolet light for 8 seconds, the cumulative light intensity on each liquid film was 36.8 mJ / cm 2 As a result, the first liquid was polymerized in the area irradiated with the ultraviolet light, forming a particulate layer made of a hardened product of the dispersed particles.

[0094] <Drying the film> Next, the film after UV exposure was naturally dried at room temperature (22°C, 49% RH) for 90 minutes, thereby removing water from the film.

[0095] <Establishing the pattern> Finally, the total light dose for the dried film was 414 mJ / cm 2 (=4.6mW / cm 2 The entire surface was exposed to ultraviolet light for 100 s (×90 s). This allowed the pattern to be fixed. In this manner, a patterned film was formed.

[0096] <Imaging the surface of a patterned film> The surface of each patterned film was photographed using a digital camera (HOZAN L-835) equipped with a zoom lens (HOZAN L-815). Some of the images thus obtained are shown in Figure 19. The patterned films were photographed by placing a piece of black paper on the back of the slide glass on which the pattern was formed.

[0097] <Imaging the cross section of a patterned film> First, each pattern film was peeled off from the slide glass using tweezers. Next, each pattern film was folded to produce a fracture surface. For pattern films with high porosity and fragility, a cross section was formed using a razor. Next, each pattern film with a cross section was fixed to a sample stage for cross-section observation with double-sided carbon conductive tape, and gold was sputtered onto the tape. In this manner, samples for observation with a scanning electron microscope (SEM) were prepared. Then, the cross sections of each sample were photographed with the SEM. The images obtained in this manner are shown in Figures 14 to 16.

[0098] Fig. 14 is a scanning electron microscope photograph showing a cross section of a line and space pattern formed by changing the line width and space width using the first emulsion, Fig. 15 is a scanning electron microscope photograph showing a cross section of a line and space pattern formed by changing the line width and space width using the second emulsion, and Fig. 16 is a scanning electron microscope photograph showing a cross section of a line and space pattern formed by changing the line width and space width using the third emulsion.

[0099] <Image analysis> Image analysis was performed using the image processing software Image J. Specifically, in each image of the cross section of the patterned film, an area that did not include any contrast noise such as broken parts was selected. Then, for each selected area, the standard deviation of the density distribution in a 256-level grayscale was extracted as a feature. Note that if there are no pores (gaps between particles) in the selected area, the standard deviation is small, and the more pores there are, i.e., the higher the porosity, the larger the standard deviation becomes.

[0100] In addition, for each image of the pattern film surface, the standard deviation of the density distribution in the 256-tone gray scale was obtained by the same method as above. Furthermore, the average density was calculated from this density distribution and used as an index of the whiteness of the pattern film surface.

[0101] <Result 1> 14 to 16, the pattern film becomes porous when the ratio of line width to space width (L / S ratio) is 1 to 1.5 or more. This tendency does not depend on the average particle size of the emulsion.

[0102] Figure 17 shows the density distribution obtained by image analysis of a portion of the photograph in Figure 15. As shown in Figure 17, when the ratio of line width to space width is small (L / S ratio = 1), the density, i.e., brightness, of the image of the cross section of the patterned film is distributed in a relatively narrow range. In contrast, when the ratio of line width to space width is large (L / S ratio = 3), the density of the image of the cross section of the patterned film is distributed in a relatively wide range.

[0103] Table 2 shows the standard deviation of the concentration distribution obtained by image analysis of the photographs in Figures 14 to 16. Also, Figure 18 shows the influence of the ratio of the line width to the space width on the standard deviation of the concentration distribution obtained by image analysis of the photographs in Figures 14 to 16.

[0104] [Table 2]

[0105] As shown in Table 2 and Figure 18, regardless of which of the first to third emulsions is used, the larger the line width to space width (L / S ratio) is, the larger the standard deviation of the concentration distribution obtained for the image of the cross section of the patterned film is. Also, the smaller the average particle size of the emulsion is, the larger the effect of the L / S ratio on the standard deviation is.

[0106] 14 to 16 and FIG. 18, it is found that there is a positive correlation between the porosity of the patterned film and the standard deviation of the concentration distribution obtained from the image of the cross section of the patterned film. From the above, it is found that the standard deviation of the concentration distribution obtained from the image of the cross section of the patterned film can be an indirect index of the porosity of the patterned film.

[0107] <Result 2> Table 3 shows the average density values ​​obtained by image analysis of the photograph in Fig. 19. Also, Fig. 20 shows the effect of the ratio of line width to space width on the average density values ​​obtained by image analysis of the photograph in Fig. 19.

[0108] [Table 3]

[0109] As shown in Table 3 and Figure 20, regardless of which of the first to third emulsions is used, the larger the ratio of line width to space width (L / S ratio), the higher the average density value obtained for the image of the pattern film surface. That is, the higher the L / S ratio, the higher the light scattering property of the pattern film. Also, the smaller the average particle size of the emulsion, the higher the average density value obtained for the image of the pattern film surface.

[0110] 19 and 20, it is apparent that there is a positive correlation between the whiteness of the pattern film and the average value of the density obtained for the image of the pattern film surface.

[0111] Tables 4 to 6 show the standard deviation of the concentration distribution obtained by image analysis of the photographs of Figures 14 to 16, and the average concentration value obtained by image analysis of the photograph of Figure 19. Also, Figure 21 shows the relationship between the standard deviation of the concentration distribution obtained by image analysis of the photographs of Figures 14 to 16, and the average concentration value obtained by image analysis of the photograph of Figure 19.

[0112] [Table 4]

[0113] [Table 5]

[0114] [Table 6]

[0115] As shown in Tables 4 to 6 and FIG. 21, there is a positive correlation between the standard deviation of the concentration distribution obtained from the image of the cross section of the pattern film and the average concentration obtained from the image of the surface of the pattern film. [Explanation of symbols]

[0116] Reference Signs List 1: substrate, 2: pattern film, 2a: film made of emulsion, 3: layer, 4: adhesive layer, 5: colorant, 21a: dispersed particles, 21a': combined body, 21b: granular layer, 21b1: hardened product of dispersed particles, 21b2: polymerized phase, 22: dispersion medium.

Claims

1. A patterned film comprising a plurality of portions with different pattern densities, one or more of the plurality of portions being porous, and one or more of the remaining portions having a lower pattern density and porosity compared to one of the one or more portions that is porous.

2. The patterned film of claim 1 , wherein one or more of the plurality of portions is non-porous.

3. 3. The patterned film according to claim 1, wherein the line width is in the range of 10 μm to 5 mm.

4. 4. The pattern film according to claim 1, wherein the height difference is in the range of 10 μm to 2 mm.

5. An article comprising the pattern film according to claim 1 and a substrate supporting the pattern film.

6. 6. The article of claim 5, further comprising a layer attached to said substrate with said patterned film sandwiched therebetween.

7. 7. The article according to claim 5 or 6, further comprising a colorant carried on the patterned film.